Consumer Environmental Attitude and Willingness to Purchase Environmentally Friendly Products: An SEM Approach. (June 2017) - Malik, Chirag; Singhal, Neeraj
It has been found that in spite of showing concern for the environment and advocating environmentally safe activities, the Indian consumer is still not ready to accept the hard truth that it the responsibility of one and all to minimize their contribution to the overall environmental pollution. This article aims at studying socio-psychological factors which contribute in the formation of environmental attitude of consumers. It further aims at establishing the connection between environmental attitude of the consumer and his/her willingness to buy environmentally friendly products (WTB-EFPs). A conceptual model has been proposed and tested using structural equation modelling (SEM). It has been found that the dimensions, such as environmental knowledge (EK), perceived seriousness of environmental (PSE) problem, interpersonal influence (IPI), collectivism and long-term orientation (LTO), have positive relationship with consumer environmental attitude (CEA). It has also been observed that consumer with favourable environmental attitude expresses their WTB-EFPs. This is an original study conducted for the first time in India using five antecedents of CEA with the application of SEM. No demographic factors have been studied in this article in order to put more focus on their socio-psychological dimensions.